A new approach to forensic medical typing of human mitochondrial DNA with the use of mass-spectrometric analysis of amplified fragments: PLEX-ID automated genetic analysis system - Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2010)
A new approach to typing human mitochondrial DNA (mtDNA) is described using multiplex PCR in combination with genetic analysis assisted by high performance mass-spectrometry based on an automated PLEX-ID ESI-TOF analyzer (Abbot Molecular, USA). The proposed test-system is designed for DNA analysis in a standard 96-well plate and allows to simultaneously treat up to 12 samples. All stages of the analysis are fully automated, from preparation and purification of amplicons to quality control and interpretation of final results. The in-built software makes possible comprehensive analysis of the data obtained including decoding of primary results; search for, comparison and registration of polymorphism profiles in relevant databases, both directly in the nucleotide composition format and indirectly in the form of nucleotide sequences. The entire process from sample preparation to final report takes less than 8 hours to be completed. It is concluded that the PLEX-ID analytical system may be used to resolve complex problems due to the possibility to combine gene typing and individualization of the biological sample in the framework of a single analytical process starting from the sampling procedure.